2013
DOI: 10.1590/s0004-27302013000700003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of PPARA, RXRA, NR1I2 and NR1I3 gene polymorphisms on the lipid-lowering efficacy and safety of statin therapy

Abstract: OBJECTIVE: The aim of the present study was investigate the association between six genetic variants in the nuclear receptor genes PPARA, RXRA, NR1I2 and NR1I3 and the lipid-lowering efficacy and safety of statin therapy. SUBJECTS AND METHODS: The study was carried out on 240 Brazilian hypercholesterolemic patients on simvastatin and atorvastatin therapy. The polymorphisms were analyzed by PCR-based methods. RESULTS: The NR1I3 rs2307424 genotype distribution was different between subjects with and without adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…A previous study has reported that dietary magnesium could reduce lipid accumulation in yellow catfish through PPARα pathway. Some other studies indicated that fenofibrate, a drug used for the treatment of hyperlipidemia, could promote the cellular cholesterol efflux by phos-phorylating PPARα [37, 38]. Earlier studies would fit nicely with the present results regarding the downregulation of SR-A and CD36 and upregulation of ABCA-1 and ABCG-1 by NXT, accompanied by increased PPARα protein expression.…”
Section: Discussionsupporting
confidence: 88%
“…A previous study has reported that dietary magnesium could reduce lipid accumulation in yellow catfish through PPARα pathway. Some other studies indicated that fenofibrate, a drug used for the treatment of hyperlipidemia, could promote the cellular cholesterol efflux by phos-phorylating PPARα [37, 38]. Earlier studies would fit nicely with the present results regarding the downregulation of SR-A and CD36 and upregulation of ABCA-1 and ABCG-1 by NXT, accompanied by increased PPARα protein expression.…”
Section: Discussionsupporting
confidence: 88%
“…We also observed from the literatures that a number of genes that appeared in the list of interacted genes with five traits had major genetic effects with single trait. Many reports showed that CETP , LIPC and LIPG were associated with HDL and LDL [ 60 62 ] and that MTHRR had known main effects for LDL [ 63 ] and blood pressure [ 64 ], NR1I3 for lipid metabolism [ 65 ], PLTP for LDL [ 66 ],[ 67 ], FOXO1 for LDL [ 68 ] and hypertension [ 69 ], SMAD9 for hypertension [ 70 ], and CSMD1 for SBP [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…NR1I2 (c.-1663T>C, c.-22-7659T>C), NR1I3 (c.540C>T, c.238+1099A>G), PPARA (c.484C>G) and RXRA (Indel -/A) did not influence lipid-lowering response to these statins. NR1I3 c.540TT genotype carriers had lower risk for statin-induced liver or muscle ADR, but the other variants were not associated with safety of statins (Lima et al, 2013).…”
Section: Drug Metabolizing Enzymes and Transportersmentioning
confidence: 89%